Pengembangan Instrumen Penilaian Berbasis Pendekatan Saintifik Kelas IV SD Muatan IPA pada Subtema Hewan dan Tumbuhan di Lingkungan Rumahku - Yetty Fatri Dewi; Rayandra Asyhar; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
The purpose of this study was to develop an instrument to measure the knowledge and skills of fourth grade students in conducting scientific activities on the sub-theme of animals and plants around my house. The instrument consists of a number of items that lead the students to scientific activities (e.g.observe, ask, gather information, process and communicate information) that is equipped by a scoring rubric. The development model used is a model 4-D consists of 4 stages, namely define, design, develop, and desimanate. The validation and limited testing result shows that the scientific approach based-assessment instrument is feasible to use. The developed instruments can be used to evaluate the learning process and assists teachers in developing the competences of the students’s knowledge and skills in conducting scientific activities.